Strategi Efektif Untuk Implementasi Keamanan Siber di Era Digital - Muhamad Febrian Aska; Deo Pratama Putra; Sinambela, Caroline Julyana Magdalena (Program Studi Informatika, Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2024)
In today's rapidly developing digital era, cyber security has become an urgent need for organizations to protect their data and information systems from increasingly complex threats. Universities are no different; in order to make their educational offerings more competitive, they must raise the caliber of their offerings. competitive. One way that institutions use information technology. The Academic Information System (AIS) is used. SIA was created to fulfill the learning process's goals, which are a component of fulfilling the college's vision and mission. fulfillment of higher education's goal and mission. Technological advances enable various cyber attacks that can result in significant losses, both in terms of finances and organizational reputation. In this context, a layered security approach and increasing awareness and competence of human resources (HR) are important strategies to achieve optimal levels of protection. This research aims to identify and analyze effective strategies that can be applied in implementing cyber security to protect organizations from various digital threats. The research method used is qualitative, which collects and analyzes interview results and related literature to understand the best approaches in cyber security. The research results show that the combination of layered security technologies such as firewalls, intrusion detection systems and data encryption, as well as security awareness training for employees, can increase an organization's resilience to cyber attacks. This approach is not only effective in resisting technical attacks but also strengthens the security culture at all levels of the organization.